2023
DOI: 10.24266/2573-5586-41.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Greater Appeal of Native Plants for Environmentally Conscious Consumers

Abstract: Native plants are increasingly of interest to growers, wholesalers, and retailers as they seek to expand sales in this important plant category. A recent online survey of 2,066 Americans showed that while many consumers were interested in, and had made a purchase of, a native plant in the past 12 months, more than half believed they were either slightly or not at all knowledgeable about native plants. People who use more environmentally conscious gardening behaviors (e.g., composting, recycling containers, rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The native enthusiast cluster, which had the greatest market potential, expressed the greatest agreement with the environmental benefits of native plants, including pollinator attracting, habitat restoring, and wildlife benefitting. These results align with previous work that identified alignment between native plant importance and proenvironmental gardening practices (Rihn et al 2023). Additionally, consumer research of plant purchasers indicated a willingness to pay more for and preference for plants grown in an environmentally conscious manner (Khachatryan et al 2014;Knuth et al 2020) while concerns about the environment grow (Tyson and Kennedy 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The native enthusiast cluster, which had the greatest market potential, expressed the greatest agreement with the environmental benefits of native plants, including pollinator attracting, habitat restoring, and wildlife benefitting. These results align with previous work that identified alignment between native plant importance and proenvironmental gardening practices (Rihn et al 2023). Additionally, consumer research of plant purchasers indicated a willingness to pay more for and preference for plants grown in an environmentally conscious manner (Khachatryan et al 2014;Knuth et al 2020) while concerns about the environment grow (Tyson and Kennedy 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In turn, consumers' positive perceptions of the beauty of native plants positively impact their intent to purchase native plants (Gillis and Swim 2020). Regarding proenvironmental behavior, several studies have established a positive correlation between environmental knowledge and purchase likelihood for native plants (Narem et al 2018), environmental gardening practices and native plant purchases (Rihn et al 2023), and positive perceptions of native plants (Shaw et al 2017). To help improve consumers' knowledge of local native plants and their environmental benefits (butterfly and moth caterpillar host plants), an online native plant finder that uses consumer zip codes to identify native plant species was developed (National Wildlife Federation 2024).…”
mentioning
confidence: 99%
“…Most of the current work on consumer IPM topics focuses either on specific landscape topics that relate to IPM, such as pollinators, or on the actual retail purchase looking at the attributes of plant products (e.g., Getter et al 2016;Khachatryan et al 2020;Klingeman et al 2009;Rihn et al , 2022Rihn et al , 2023Sellmer et al 2003;Stewart et al 2002;Warner et al 2022;Wei et al 2019Wei et al , 2020Yiridoe et al 2005). However, considering that a successful IPM approach includes several components, it is critical to evaluate how consumer preferences change for each of the components (e.g., mechanical/physical controls, cultural controls, biological controls, and chemical controls) (Ehler 2006).…”
mentioning
confidence: 99%